Answer:
15u + 141 = 420
Step-by-step explanation:
So basically we are modelling how much the coach is spending. Each player is given a uniform and a basketball
We can use 'u' as the cost of a single uniform
We can use 'b' as the cost of a single basketball
Since there is 15 players we must give a ball and uniform to each so
15u + 15b = 420
The problem gives us the cost of each basketball: 9.40
so now 15u + 15(9.4) = 420
15u + 141 = 420
Answer:
4-(-10)
Step-by-step explanation:
17 less than 6+1 is negative 10 so 4 minus negative 10
-36 because 64-100 (separate the terms)
Answer:
Step-by-step explanation:
xy=-30
y=-30/x
x+y=-4
x-30/x=-4
x²-30=-4x
x²+4x-30=0
![x^2+4x-30=0\\x=\frac{-4\pm\sqrt{16+120} }{2} \\=\frac{-4\pm\sqrt{136} }{2} \\=-2\pm\sqrt{39} \\=-2+\sqrt{39} ,-2-\sqrt{39} \\y=\frac{-4}{-2+\sqrt{39} } ,\frac{4}{2+\sqrt{39} }](https://tex.z-dn.net/?f=x%5E2%2B4x-30%3D0%5C%5Cx%3D%5Cfrac%7B-4%5Cpm%5Csqrt%7B16%2B120%7D%20%7D%7B2%7D%20%5C%5C%3D%5Cfrac%7B-4%5Cpm%5Csqrt%7B136%7D%20%7D%7B2%7D%20%5C%5C%3D-2%5Cpm%5Csqrt%7B39%7D%20%5C%5C%3D-2%2B%5Csqrt%7B39%7D%20%2C-2-%5Csqrt%7B39%7D%20%5C%5Cy%3D%5Cfrac%7B-4%7D%7B-2%2B%5Csqrt%7B39%7D%20%7D%20%2C%5Cfrac%7B4%7D%7B2%2B%5Csqrt%7B39%7D%20%7D)
![correction write ~-30 ~in~place~of~-4~in~the~end](https://tex.z-dn.net/?f=correction%20write%20~-30%20~in~place~of~-4~in~the~end)
When roots of polynomials occur in radical form, they occur as two conjugates.
That is,
The conjugate of (a + √b) is (a - √b) and vice versa.
To show that the given conjugates come from a polynomial, we should create the polynomial from the given factors.
The first factor is x - (a + √b).
The second factor is x - (a - √b).
The polynomial is
f(x) = [x - (a + √b)]*[x - (a - √b)]
= x² - x(a - √b) - x(a + √b) + (a + √b)(a - √b)
= x² - 2ax + x√b - x√b + a² - b
= x² - 2ax + a² - b
This is a quadratic polynomial, as expected.
If you solve the quadratic equation x² - 2ax + a² - b = 0 with the quadratic formula, it should yield the pair of conjugate radical roots.
x = (1/2) [ 2a +/- √(4a² - 4(a² - b)]
= a +/- (1/2)*√(4b)
= a +/- √b
x = a + √b, or x = a - √b, as expected.